The Borrelia burgdorferi Adenylate Cyclase, CyaB, Is Important for Virulence Factor Production and Mammalian Infection - Ante, Vanessa M.; Farris, Lauren C.; Saputra, Elizabeth P.; Hall, Allie J.; O’Bier, Nathaniel S.; Oliva Chávez, Adela S.; Marconi, Richard T.; Lybecker, Meghan C.; Hyde, Jenny A. (Frontiers in Microbiology, 2021)
Borrelia burgdorferi, the causative agent of Lyme disease, traverses through vastly distinct environments between the tick vector and the multiple phases of the mammalian infection that requires genetic adaptation for the progression of pathogenesis. Borrelial gene expression is highly responsive to changes in specific environmental signals that initiate the RpoS regulon for mammalian adaptation, but the mechanism(s) for direct detection of environmental cues has yet to be identified. Secondary messenger cyclic adenosine monophosphate (cAMP) produced by adenylate cyclase is responsive to environmental signals, such as carbon source and pH, in many bacterial pathogens to promote virulence by altering gene regulation. B. burgdorferi encodes a single non-toxin class IV adenylate cyclase (bb0723, cyaB). This study investigates cyaB expression along with its influence on borrelial virulence regulation and mammalian infectivity. Expression of cyaB was specifically induced with co-incubation of mammalian host cells that was not observed with cultivated tick cells suggesting that cyaB expression is influenced by cellular factor(s) unique to mammalian cell lines. The 3' end of cyaB also encodes a small RNA, SR0623, in the same orientation that overlaps with bb0722. The differential processing of cyaB and SR0623 transcripts may alter the ability to influence function in the form of virulence determinant regulation and infectivity. Two independent cyaB deletion B31 strains were generated in 5A4-NP1 and ML23 backgrounds and complemented with the cyaB ORF alone that truncates SR0623, cyaB with intact SR0623, or cyaB with a mutagenized full length SR0623 to evaluate the influence on transcriptional and post-transcriptional regulation of borrelial virulence factors and infectivity. In the absence of cyaB, expression and production of ospC was significantly reduced, while the protein levels for BosR and DbpA were substantially lower than parental strains. Infectivity studies with both independent cyaB mutants demonstrated an attenuated phenotype with reduced colonization of tissues during early disseminated infection. This work suggests that B. burgdorferi utilizes cyaB and potentially cAMP as a regulatory pathway to modulate borrelial gene expression and protein production to promote borrelial virulence and dissemination in the mammalian host.